Electrochemical Performance of 1-Ethyl-3-Methylimidazolium Bis(Trifluoromethylsulfonyl)Imide Ionic Liquid as Electrolyte for Primary Mg-Air Batteries. Issue 6 (3rd April 2019) - Zhang, Jingli; Ma, Jingling; Wang, Guangxin; Li, Yaqiong; Volinsky, Alex A.
Abstract : Ionic liquids are promising electrolytes for the primary Mg-air batteries. Three electrolytes, including pure 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ionic liquid, 50 mol.% butyl acetate and 50 mol.% water were studied. Attenuated total reflectance Fourier transform infrared spectroscopy, scanning electron microscopy and electrochemical impedance spectroscopy were used to examine discharge performance and the effects of butyl acetate and water additions. Galvanostatic measurements indicate that butyl acetate is an excellent additive, which can significantly improve the battery performance by reducing electrolyte impedance by increasing conductivity. However, while water also improved electrolyte discharge performance, it was consumed by the hydrogen evolution reaction over the 72 h discharge.